(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Bean Trees is one of Barbara Kingsolver’s critically acclaimed novels that received the American Library Association Award for its special appeal to adults. The novel portrays the esthetic view of nature and culture of the people in Kentucky in a hilarious way. In this novel, the author describes the key issues which include the plight of immigrants, racism and self-identity of a woman through different characters. This paper explores the inherent importance of underlying relationship between woman and nature, and comparing the symbiotic connection between them.